Akirin2 could promote the proliferation but not the differentiation of duck myoblasts via the activation of the mTOR/p70S6K signaling pathway. (October 2016) - Sun, Wenqiang; Huang, Huilan; Ma, Shengchao; Gan, Xiang; Zhu, Mou; Liu, Hehe; Li, Liang; Wang, Jiwen
Graphical abstract: Highlights: Avian Akirin gene family comprises only one gene (Akirin2). Duck Akirin2 does not seem to be capable of regulating myoblast differentiation. Duck Akirin2 could promote myoblast proliferation. Duck Akirin2 could activate mTOR/S6K signaling pathway. A novel insight into the function of Akirin gene family was presented. Abstract: The Akirin gene family normally contains two members that are essential to myoblast differentiation. Noticeably, the avian Akirin gene family comprises only one gene (Akirin2), However, it remains unknown whether avian Akirin gene family still has the function of Akirin1; moreover, it is still unclear whether and how Akirin2 plays a role in myoblast proliferation and differentiation. Interestingly, the unexpected functions of duck Akirin2 were revealed in the present study. The Real-time PCR results showed that between 12 and 48 h during the process of duck myoblasts differentiation, the overexpression of Akirin2 did not significantly increase the expression of myogenic regulatory factors. Flow cytometry analysis revealed that the cell cycle transition was accelerated by Akirin2 overexpression. Moreover, the overexpression of Akirin2 did not influence the myotube formation. Strikingly, when duck myoblasts were cultured in the growth medium, the overexpression of Akirin2 significantly enhanced cell viability. Although the expression of cyclin-dependent proteins did not significantly increase after transfection, the expression of the mammalian targets of rapamycin (mTOR) and p70 S6 kinase (p70S6K) increased. Furthermore, the protein expression of phospho-p70S6K (Ser 417) also increased. However, when rapamycin and pEGFP-N1-Akirin2 plasmids were added together to the growth medium, the positive impact of Akirin2 on cell viability and the mRNA expression of mTOR and p70S6K were significantly blocked. Furthermore, the expression of phospho-mTOR (Ser 2448) and phospho-p70S6K (Ser 417) were also blocked. Taken together, these results could suggest that duck Akirin2 could promote myoblast proliferation via the activation of the mTOR/p70S6K signaling pathway.